2014
DOI: 10.1093/gbe/evu124
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Pretranscriptional DNA Methylation, Transcriptional Transcription Factor, and Posttranscriptional microRNA Regulations on Protein Evolutionary Rate

Abstract: Gene expression is largely regulated by DNA methylation, transcription factor (TF), and microRNA (miRNA) before, during, and after transcription, respectively. Although the evolutionary effects of TF/miRNA regulations have been widely studied, evolutionary analysis of simultaneously accounting for DNA methylation, TF, and miRNA regulations and whether promoter methylation and gene body (coding regions) methylation have different effects on the rate of gene evolution remain uninvestigated. Here, we compared hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 87 publications
(146 reference statements)
1
21
0
Order By: Relevance
“…The comparative analysis of human DNA methylome data with human-macaque and human-mouse protein evolutionary rates revealed that gene body methylation is negatively correlated with protein evolutionary rate, whereas promoter methylation correlates positively (Chuang and Chiang, 2014). Similarly, genes with heavy body methylation are evolutionarily conserved and enriched for housekeeping functions in invertebrates (Sarda et al, 2012).…”
Section: Gene Body Methylationmentioning
confidence: 99%
“…The comparative analysis of human DNA methylome data with human-macaque and human-mouse protein evolutionary rates revealed that gene body methylation is negatively correlated with protein evolutionary rate, whereas promoter methylation correlates positively (Chuang and Chiang, 2014). Similarly, genes with heavy body methylation are evolutionarily conserved and enriched for housekeeping functions in invertebrates (Sarda et al, 2012).…”
Section: Gene Body Methylationmentioning
confidence: 99%
“…In human, it was observed that the majority of gene bodies were heavily methylated (Keller et al 2016). Positiondependent correlations have also been shown between CpG methylation level and d N of the target genes (Chuang and Chiang 2014) or exons (Chuang et al 2012); such methylation-d N correlations were observed to be negative for gene bodies (or internal/last exons) and positive for promoter regions (or first exons). Accordingly, we asked whether our results shown in Figure 5 were biased toward first exons.…”
Section: Discussionmentioning
confidence: 94%
“…A follow-up study published lately showed that 65 of 24-nt miRNAs exhibited elevated CHH methylation (but not CpG methylation) around their target sites [31]. These studies imply that miRNA targeting may lead to an increased level of DNA methylation in the gene body of plants (which, in fact, was also observed in human [32]). Of note, nevertheless, each miRNA was predicted to have only one target site in the target gene.…”
Section: Discussionmentioning
confidence: 96%